La Laurentienne agricole - Bouchard, Jean (Assurances)

(untitled) (HEC Montréal, 1987)
We have asked the management of Laurentian Farm Insurance Company Inc. to discuss the nature of their business inasmuch as the founding of the company represents a relatively new and, as 1985 results will attest, very profitable enterprise. Laurentian Farm, a subsidiary of The Laurentian General, deals with agricultural concerns. In this domain, we find the initiatives taken by mutual insurance companies in municipalities, parishes and counties and whose organization was completed by the Federation which provided them with reinsurance, long unavailable to them. Thus, companies geared to agriculture, whose work methods differ from those of other types of companies, were set up and are now, in general, showing interesting results for the type of group they encompass. We felt it would be interesting to examine The Laurentian General's enterprise as opposed to the farm mutual group even if, strangely enough, Laurentian Farm itself sprang from a mutual group.